Pathological Clavicle Fracture Secondary to Breast Carcinoma After a Minor Trauma and Fixed with Open Reduction and Internal Fixation: A Case Report - Ben Murphy; Stephen Murphy; Andre McLeod; Padhraig O’Loughlin; David Morrissey (Journal of Orthopaedic Case Reports)
Introduction: This is the first reported case of breast carcinoma metastasizing to the clavicle, causing a pathological fracture and subsequently being treated with open reduction and internal fixation (ORIF). Case Report: A 60-year-old female presented with shoulder pain after a minor trauma while swimming. She had prodromal pain and a breast cancer history. The radiograph revealed a right clavicle fracture. She had ongoing pain and no union on radiographs, with concern for a pathological fracture. Bone biopsy was performed and consistent with metastatic breast carcinoma involving the clavicle. ORIF was performed for symptomatic control. A 14-month follow-up revealed a healed fracture and a full return to activity. Conclusion: A pathological clavicle fracture may be the presenting complaint of an unknown primary tumor or even signal recurrence of a previously treated malignancy. They can be challenging to diagnose and as such, we would urge surgeons to have a high index of suspicion in these cases. Excision of clavicular metastasis and partial or even full claviculectomy have been described in the literature. This is the first reported case of breast carcinoma metastasizing to the clavicle, causing a pathological fracture and subsequently being treated with ORIF. We would suggest that surgeons faced with this issue in the future consider it as a surgical option for pain relief and restoration of function in the otherwise fit and active patient.